A Concept for a Japanese Regulatory Framework for Emerging Medical Devices with Frequently Modified Behavior - Nagomi Ota; Keisuke Tachibana; Tetsuya Kusakabe; Shoji Sanada; Masuo Kondoh (Wiley, 2020)
Recent progress in the Internet of Things and artificial intelligence has made it possible to utilize the vast quantity of personal health records, clinical data, and scientific findings for prognosis, diagnosis, and therapy. These innovative technologies provide new possibilities with the development of medical devices (MDs), whose behaviors can be continuously modified. A novel regulatory framework covering these MDs is now under discussion in Japan. In this review, we introduce the regulatory initiative for MDs and the importance of a paradigm shift from regulation to innovation regarding MDs.